Short term persistence of human papillomavirus and risk of cervical precancer and cancer: population based cohort study. (28th July 2009) - Castle, Philip E; Rodríguez, Ana Cecilia; Burk, Robert D; Herrero, Rolando; Wacholder, Sholom; Alfaro, Mario; Morales, Jorge; Guillen, Diego; Sherman, Mark E; Solomon, Diane; Schiffman, Mark; ,
Abstract : Objective To evaluate the cumulative incidence of cervical intraepithelial neoplasia II or worse (grade II+) or cervical intraepithelial neoplasia grade III+ after short term persistence of prevalently detected carcinogenic human papillomavirus (HPV). Design Population based cohort study. Setting Guanacaste, Costa Rica. Participants 2282 sexually active women actively followed after enrolment. Main outcome measures Primary end points: three year and five year cumulative incidence of histologically confirmed cervical intraepithelial neoplasia grade II+ (n=70). Cervical specimens collected at each visit tested for more than 40 HPV genotypes. HPV 16, 18, 26, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68, 73, and 82 were considered the primary carcinogenic genotypes. Results Women who tested positive for a carcinogenic HPV at enrolment and after about one year (9-21 months) (positive/positive) had a three year cumulative incidence of cervical intraepithelial neoplasia grade II+ of 17.0% (95% confidence interval 12.1% to 22.0%). Those who tested negative/positive (3.4%, 0.1% to 6.8%), positive/negative (1.2%, −0.2% to 2.5%), and negative/negative (0.5%, 0.1% to 0.9%) were at a significantly lower risk. There was little difference in the cumulative incidence of cervical intraepithelial neoplasia grade II+ between testing positive twice for any carcinogenic HPV genotype (same genotype or different genotypes) v testing positive twice for the same carcinogenic genotype (17.0% v 21.3%, respectively). Short term persistence of HPV 16 strongly predicted cervical intraepithelial neoplasia grade II+, with a three year cumulative incidence of 40.8% (26.4% to 55.1%). Similar patterns were observed for the five year cumulative incidence of grade II+ and for three year and five year cumulative incidence of grade III+. Conclusions Short term persistence of a prevalently detected carcinogenic HPV infection, especially HPV 16, strongly predicts a subsequent diagnosis of cervical intraepithelial neoplasia II+ over the next few years.